2021
DOI: 10.1094/pdis-03-20-0508-re
|View full text |Cite
|
Sign up to set email alerts
|

Difenoconazole Resistance Shift in Botrytis cinerea From Tomato in China Associated With Inducible Expression of CYP51

Abstract: Gray mold caused by Botrytis cinerea is one of the most important diseases in tomato. It can be controlled effectively by demethylation inhibitor (DMI) fungicides, but their resistant status is unclear after long-term use in the field. Baseline sensitivity to difenoconazole of 142 B. cinerea isolates from China with no history of DMI usage was characterized, with a mean EC50 of 0.97 ± 0.50 μg/mL. EC50 values to difenoconazole of another 248 isolates collected in 2011 and 2016 ranged from 0.04 to 11.99 μg/mL, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…In addition, no cross-resistance was discovered in this investigation between DMI and non-DMI fungicides. This is consistent with the reported results of Botrytis cinerea and Colletotrichum gloeosporioides resistance to DMIs 16 , 37 . In the experiment of cross resistance, we found that there were a small number of isolates with multifungicide resistance (MFR).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, no cross-resistance was discovered in this investigation between DMI and non-DMI fungicides. This is consistent with the reported results of Botrytis cinerea and Colletotrichum gloeosporioides resistance to DMIs 16 , 37 . In the experiment of cross resistance, we found that there were a small number of isolates with multifungicide resistance (MFR).…”
Section: Discussionsupporting
confidence: 93%
“…According to the report of Rallos, overexpression of CYP51 was associated with the presence of the Y136F mutant genotype 45 . However, the underlying mechanisms of CYP51 overexpression are not known for in the field DMI-resistant subpopulations of Puccinia triticina 43 , Sclerotinia homoeocarpa 51 , Pyrenophora teres 17 , Colletotrichum gloeosporioides 16 , and Botrytis cinerea 37 . We tried to clone and sequence analysis the promoter of LtCYP51 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no cross-resistance was discovered in this investigation between DMIs and non-DMIs fungicides. This matches reports of Botrytis cinerea and Colletotrichum gloeosporioides resistance to DMIs 16,37 . The commonly used site-speci c fungicides (such as carbendazim and azoxystrobin) gave bad control effect against L. theobromae due to the development of resistant isolates.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a 199-bp sequence duplication was discovered at the promoter of CYP51 of Penicillium digitatum 45 . However, underlying mechanisms of CYP51 overexpression are not known for in the eld DMI-resistant subpopulations of Puccinia triticina 39 , Sclerotinia homoeocarpa 46 , Pyrenophora teres 17 , Colletotrichum gloeosporioides 16 , Botrytis cinerea 37 . We tried to clone and sequence analysis the promoter of LtCYP51 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the CYP51 gene are a common cause of resistance to DMIs and have been found in several other pathogens [36,41,42]. Overexpression of the CYP51 genes is also commonly found in resistant isolates of various pathogens [43][44][45]. We anticipated either mutations or overexpression of the CYP51 gene to be the cause of the resistance, and we found mutations and overexpression to be present in DMI-resistant isolates of V. effusa.…”
Section: Discussionmentioning
confidence: 76%